PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN DAN SUB SEKTOR BATUBARA - Adelia Kharisma Sularto; Rilla Gantino (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to analyze the influence of the board of directors, audit committee, institutional ownership, and managerial ownership on the financial performance of food and beverage sub-sector companies and coal sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The board of directors is measured by the number of members of the board of directors in the company. The audit committee is measured by the number of members of the audit committee in the company, institutional ownership is measured by the percentage of institutional ownership in the company, and managerial ownership is measured by the percentage of ownership of managers in the company. The company's performance is proxied by Return on Assets (ROA) with the formula net profit divided by total assets. The method used in this research is purposive sampling. The data is quantitative data based on secondary data in the form of financial statements. The data analysis method used is multiple linear data analysis. The results of hypothesis testing indicate that the board of directors, audit committee, institutional ownership, and managerial ownership have a significant effect on the company's financial performance in food and beverage sub-sector companies and coal sub-sector companies.